Influence of an extended incubation period on values of minimum inhibitory concentrations of antibiotics in Stenotrophomonas maltophilia clinical strains - Hejnar, P; Hamal, P; Koukalová, D (The new microbiologica, 2000)
In 106 Stenotrophomonas maltophilia clinical strains the susceptibility to 19 kinds of antibiotics was tested by the broth dilution micromethod at 24 h and 48 h incubation. Isolated strains demonstrated the lowest frequency of resistance to cotrimoxazole (7.5% of resistant strains at 24 h incubation and 18.9% at 48 h), ofloxacin (13.2% and 30.2%), ciprofloxacin (19.8% and 50.9%) and to cefoperazone/sulbactam (20.8% and 37.7%). The smallest growth of the number of resistant strains after extended incubation was recorded in gentamicin (by 10.4%), ceftazidime (by 11.3%) and cotrimoxazole (by 11.4%). On the contrary, the largest growth of resistance was demonstrated in cefoperazone and ciprofloxacin (by 31.1%). Average values of the growth of minimum inhibitory concentrations (MICs) were lowest in ciprofloxacin and ofloxacin (2.3 times) and highest in piperacillin/tazobactam (4.5 times) and piperacillin (5.0 times). As far as the stability of MIC is concerned, the largest occurrence of strains with the MIC growth doubled as a maximum was found in ceftazidime (78.4%), ofloxacin (76.1%) and ciprofloxacin (75.3%), the smallest in piperacillin/tazobactam (43.2%) and piperacillin (38.9%). The importance of incubation extended to 48 h during the testing of S. maltophilia strains was noted for correctly setting their susceptibility to antibiotics.
Keywords: gramnegativní bakteriální infekce; Humans; Anti-Bacterial Agents; Gram-Negative Bacterial Infections; mikrobiální testy citlivosti; Stenotrophomonas maltophilia; Drug Resistance, Microbial; antibakteriální látky; antibiotická rezistence; Cross Infection; Microbial Sensitivity Tests; infekce spojené se zdravotní péčí; lidé